2000
DOI: 10.1103/physrevb.61.r7873
|View full text |Cite
|
Sign up to set email alerts
|

Probing the polarity of ferroelectric thin films with x-ray standing waves

Abstract: An x-ray-diffraction method that directly senses the phase of the structure factor is demonstrated and used for determining the local polarity of thin ferroelectric films. This method is based on the excitation of an x-ray standing-wave field inside the film as a result of the interference between the strong incident x-ray wave and the weak kinematically Bragg-diffracted x-ray wave from the film. The method is used to sense the displacements of the Pb and Ti sublattices in single-crystal c-domain PbTiO 3 thin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(20 citation statements)
references
References 14 publications
0
20
0
Order By: Relevance
“…Studies of thicker PbTiO 3 films on SrTiO 3 substrates 24,36 have found that the polarity can be either up or down, suggesting that the sign may depend on film thickness. For ultrathin films, such as those studied here, there may be a stronger preference for up polarization.…”
Section: Discussionmentioning
confidence: 98%
“…Studies of thicker PbTiO 3 films on SrTiO 3 substrates 24,36 have found that the polarity can be either up or down, suggesting that the sign may depend on film thickness. For ultrathin films, such as those studied here, there may be a stronger preference for up polarization.…”
Section: Discussionmentioning
confidence: 98%
“…While first-principles theory [15,[17][18][19] has confirmed that ionic compensation of surfaces is expected to be sufficient to stabilize polar phases in ultrathin ferroelectric films, the simple extrapolations used to apply these results to nonzero temperatures have not taken into account the ferroelectric phase transition. To date most experiments on ultrathin ferroelectrics have been performed either in air [15,[22][23][24][25][26] or in vacuum conditions [3,[26][27][28], often without accounting for the possible large difference in equilibrium polarization stability. These considerations motivate the present work, the first determination of the equilibrium polarization phase diagrams of ultrathin ferroelectric films as a function of temperature and the external chemical potential controlling their ionic surface compensation.…”
mentioning
confidence: 99%
“…18 Recently, this method has been extended to compound thin films with the thicknesses less than the extinction length, i.e., when the x-ray diffraction becomes kinematical. 14,15,19,20 The standing wave in thin film is generated via the interference between the strong incident wave and the weak kinematically diffracted wave from the film resulting in much weaker XSW modulations in comparison with perfect bulk crystals. One distinct advantage of the thin film XSW method is the broadening of the rocking curve that makes it possible to study a variety of crystalline materials that cannot be grown as bulk perfect crystals.…”
Section: Resultsmentioning
confidence: 99%
“…7 Recently, this technique was also used to study polarity of thin ferroelectric films. 15 In this work we combined the XSW method with high-resolution x-ray diffraction to study the crystalline perfection and the polarity of the GaN epitaxial film grown by the hydride vapor phase epitaxy on Si-face SiC.…”
Section: Introductionmentioning
confidence: 99%